Perinatal outcomes of intrauterine insemination/clomiphene pregnancies represent an intermediate risk group compared with in vitro fertilisation/ intracytoplasmic sperm injection and naturally conceived pregnancies - Poon, W.B. (2016)
10.1111/jpc.12257